(untitled) (Journal of actual problems of jurisprudence, 2019)
Article is devoted to consideration of the bank guarantee as a way of providing performance of obligations in civil law. The law, and the agreement of subjects of a civil turn, envisage various ways of providing obligations. The legislation carries to such ways the bank guarantee, which is not accessory way of providing performance of obligations. The bank guarantee is emerging institute of domestic civil law, and is urged to serve the relations of businessmen at commission of large commercial deals by them, and creates the most reliable mechanism of their providing. Key words: obligations, obligations law, methods of providing performance of obligations, guarantee, bank guarantee, guarantor, responsibility.